Socialization of Factors that Influence Exclusive Breastfeeding Practices and Their Implications for Stunting Prevention in Tasikmalaya City, West Java, Indonesia - Dewi Ratnasari; fahmi sidiq (Research Collaboration Community (RCC), 2024)
Stunting is still a national health problem in Indonesia, and one of the contributing factors is the lack of exclusive breastfeeding practices. This research aims to analyze the factors that influence the practice of exclusive breastfeeding in Tasikmalaya City, West Java. The case-control method was used in this research involving 4 Community Health Centers in Tasikmalaya City. Data was collected from mothers with children aged 6-12 months who were exclusively breastfed and those who were not exclusively breastfed. The research results show that husband's support has a significant influence on the success of exclusive breastfeeding practices. Apart from that, maternal knowledge also influences the perception of breast milk insufficiency. Other factors such as IMD practices and media exposure did not show a significant relationship. Re-socialization efforts are needed regarding the importance of exclusive breastfeeding, increasing mothers' knowledge, as well as actively involving fathers' groups in programs to increase exclusive breastfeeding.